Kompetensi Pengadilan Agama Terhadap Penyelesaian Sengketa Perbankan Syariah Berdasarkan Hukum Islam - Muchtar A. H. Labetubun (Faculty of Law, Universitas Pattimura, 2012)
That moment Religion Court as Section 49 letter (i) Law Number 3 Year 2003 about Religion Court, having absolute authority judge economic case of Moslem law banking included Moslem law Banking, of course this matter give paradigm differ in solving of Moslem law banking dispute compared to before existence of the law (Act No.7/1989). So that the solving of Moslem law banking dispute follow rule Islamic Law among others Jurisdiction (Wilayat Al-Qadla), peace/deliberation (Sulh/Ishlah), and Arbitrase (Tahkim), according to agreement in akad by the parties. This matter because of Moslem law Banking represent economic institution which in its execution use Islamic law principles.